Latent myofascial trigger points injection therapy for adult cough variant asthma: A randomized controlled trial - Liu, Qianqian; Zhang, Wenwen; Tian, Tian; Liu, Yu; Bai, He; Hu, Qiya; Qi, Feng (Frontiers in Medicine, 2023)
Background: Cough variant asthma (CVA) is a chronic inflammatory airway disease characterized by airway hyper-responsiveness (AHR), of which cough is the only symptom. The cough is a result of the contraction of the vocal cords, diaphragm, sternocleidomastoid muscle and other respiratory related muscles caused by the AHR. Long-term chronic coughing can lead to repetitive contraction and chronic strain of the muscles involved in the head and neck, ultimately contributing to the formation of latent myofascial trigger points (MTrPs). In turn, latent MTrPs can also irritate or compress the nerves around them, triggering cough. The date indicated that latent MTrPs can induce autonomic phenomena and are effective in allergic rhinitis. But their roles in asthma are unclear. In this article, the efficacy and safety of latent MTrPs injection therapy in CVA were investigated. Methods: This randomized controlled trial was conducted with 110 patients. Patients were assigned to the intervention or control group in a 1:1.5 ratio. Intervention group (n=44): single injection therapy with latent MTrPs. Control group (n=66): budesonide-formoterol plus montelukast for eight weeks. During the 36-week follow up period, the recurrence rate at week 36, cough visual analog scale (VAS), ACT (asthma control test)-scores, ACQ5 (asthma control questionnaire)-scores, AQLQ (asthma quality of life questionnaire)-scores, proportion of using rescue medication, and adverse events were evaluated. Results: The recurrence rate at week 36 was lower in the intervention group than in the control group (36w, 5.0% vs. 34.55%, P=0.001). There were significant differences between groups in change from baseline to 36 weeks in VAS [36w, 1.70 (1.49) vs. 3.18 (2.04), P<0.001]; ACT-score [36w, 21.38 (2.65) vs. 18.53 (3.00), P<0.001]; ACQ5-score [36w, 0.85 (0.55) vs. 1.52 (0.62), P<0.001]; AQLQ-score [36w, 174.40 (18.22) vs. 151.69 (24.04), P<0.001]; proportion of using rescue medication (36w, 5.0% vs. 29.1%, P=0.003). Fewer adverse events occurred in the two groups. Conclusion: Latent myofascial trigger points injection therapy provided long-acting, practical, short treatment duration and safety methods for CVA.